Law on Andean Tariff Preferences and the FTAA Process - Fairlie, Alan (2016)
The author studies the Andean Trade Preferences Act (ATPA), a U.S. unilateral trade policy toward the Andean region (except Venezuela) aimed at promoting Andean exports to U.S. markets and the substitution of illegal crops The article explores the implications of this Act, and analyzes different views on its efficacy. It highlights some perspectives that argue that the ATPA has not influenced production or export patterns of Andean countries, and others that consider this law as a feasible way of increasing investment flows and exports between the U.S. and the Andes.